A frugal arduino-based spirometer for low-resource settings: design, development and validation of a preliminary prototype - Wallace, James; Checa Rifá, Pedro; Kannathasan, Thanusan; Hayfron-Benjamin, Charles F.; Anyanwu, Philip; Piaggio, Davide (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundMedical devices are essential for maintaining resilient health systems worldwide. However, their distribution does not reflect this, with as many as 76% of devices being used by 13% of the world’s population. Most devices, being designed for High-Income countries (HICs) and failing to consider the local needs of other settings, often fail when deployed in other contexts. Spirometers particularly are underutilised in these regions despite high respiratory disease burden. This study aims to develop and validate a frugal affordable spirometer for low-resource settings (LRSs).MethodsA Venturi-style spirometer was designed using 3D printed components, low-cost electronics such as the Arduino nano (ESP32) and differential pressure sensor (MXP5010DP), and software such as MATLAB and Arduino IDE. The device was validated through a 2-L pump test and a prospective evaluation study involving 30 participants, comparing its performance to a CE marked spirometer. Key metrics included were the mean absolute error (MAE), mean absolute percentage error (MAPE), Pearsons’s correlation, and Intraclass correlation coefficients (ICC).ResultsThe device was successfully 3D printed from Polylactic acid (PLA) using an Ultimaker 2+ printer and assembled with electronic components. The device achieved a MAP error of 1.53% in the pump test. In the prospective evaluation study, the device showed strong agreement for forced expiratory volume in 1 s (FEV1) with the benchmark device (ICC = 0.97, r = 0.97, p < 0.001). Peak expiratory flow (PEF) measurements were less accurate (MAPE = 18.01%) but still demonstrated strong correlation (ICC = 0.80, r = 0.89). This accuracy was in line with the International Standards Organisation 26782:2009 standards for accurately measuring volume.ConclusionThis study designed, prototyped and validated a spirometer that can be used as a lung screening tool, that achieves high accuracies comparable to those of other portable spirometers. This study also validated that frugal engineering could reduce the cost of devices without affecting the clinical accuracy. Whilst promising, further validation with clinical populations and better alignment with regulatory standards are needed before use in LRSs.